2007
DOI: 10.1152/ajpheart.00087.2006
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive, but not reactive, spinal cord stimulation mitigates transient ischemia-induced myocardial infarction via cardiac adrenergic neurons

Abstract: Our objective was to determine whether electrical neuromodulation using spinal cord stimulation (SCS) mitigates transient ischemia-induced ventricular infarction and, if so, whether adrenergic neurons are involved in such cardioprotection. The hearts of anesthetized rabbits, subjected to 30 min of left anterior descending coronary arterial occlusion (CAO) followed by 3 h of reperfusion (control), were compared with those with preemptive SCS (starting 15 min before and continuing throughout the 30-min CAO) or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 30 publications
6
91
0
1
Order By: Relevance
“…Catecholamines have also been reported to protect heart from transient myocardial ischemia-induced apoptosis mediated by α 1 -PKC pathway and ß-PKA pathway (Broadley and Penson, 2004;). A recent study also reported that this cardioprotection was dependent on cardiac adrenergic efferent neurons (Southerland et al, 2006). Other neuropeptides, such as NO (Sanada and Kitakaze, 2004) and beta-endorphin are potentially released during SCS and also may prevent myocardial ischemia.…”
Section: 26mentioning
confidence: 88%
See 4 more Smart Citations
“…Catecholamines have also been reported to protect heart from transient myocardial ischemia-induced apoptosis mediated by α 1 -PKC pathway and ß-PKA pathway (Broadley and Penson, 2004;). A recent study also reported that this cardioprotection was dependent on cardiac adrenergic efferent neurons (Southerland et al, 2006). Other neuropeptides, such as NO (Sanada and Kitakaze, 2004) and beta-endorphin are potentially released during SCS and also may prevent myocardial ischemia.…”
Section: 26mentioning
confidence: 88%
“…Recently, it was proposed that SCS stabilizes the intrinsic cardiac nervous system and improves cardiac function (Foreman et al, 2000;Armour et al, 2002;Cardinal et al, 2006). Pre-emptive SCS is likely to protect myocardium from effects of critical ischemia (Southerland et al, 2006). Importantly, there is no solid evidence that SCS has the capability to augment local blood flow in the heart, which is different from the SCS effects on the limbs and brain (Norrsell et al, 1998;Kingma et al 2001).…”
Section: 15mentioning
confidence: 99%
See 3 more Smart Citations